Cardiometabolic vigilance in COVID-19 and resource husbandry in resource-challenged times: Clinical practice- based expert opinion. Issue 1 (January 2021) - Das, Ashok Kumar; Kalra, Sanjay; B, Krishnakumar; Sharma, Kamal; John, Mathew; Nair, Tiny; Shaikh, Shehla; Khandelwal, Deepak; Priya, Gagan; Dutta, Deep; Gangadhar, Prathosh; Dhingra, Atul; et al.
Abstract: Background and aims: The ongoing pandemic of coronavirus disease 2019 (COVID-19) is rapidly evolving, thereby posing a profound challenge to the global healthcare system. Cardiometabolic disorders are associated with poor clinical outcomes in persons with COVID-19. Healthcare challenges during the COVID-19 pandemic are linked to resource constraints including shortage of Personal Protective Equipment's (PPE), laboratory tests and medication. In this context, a group of clinical experts discussed the endocrine and cardiology vigilance required in times of COVID-19. Further, the group proposed certain resource husbandry recommendations to be followed during the pandemic to overcome the constraints. Method: The clinical experts discussed and provided their inputs virtually. The expert panel included clinical experts comprising endocrinologists, Consultant Physicians and cardiologists from India. The panel thoroughly reviewed existing literature on the subject and proposed expert opinion. Results: The expert panel put forward clinical practice-based opinion for the management of cardiometabolic conditions including diabetes mellitus and hypertension. As these conditions are associated with poor clinical outcomes, the expert panel recommends that these persons be extra-cautious and take necessary precautions during the ongoing pandemic. Further, experts also provided appropriate, affordable, available and accessible solution to the resource constraint situations in times of COVID-19 pandemic. Conclusion: The clinical expert opinion put forward in this article will serve as a reference for clinicians treating diabetes and cardiovascular disease during the COVID-19 pandemic. Highlights: Healthcare challenges during the pandemic are linked to resource constraints including shortage of PPE, laboratory tests and medications A group of clinical experts discussed the endocrine and cardiology vigilance required in times of COVID-19 The expert panel put forward clinical practice-based opinion for the management of cardiometabolic conditions This will serve as a reference for clinicians treating diabetes and cardiovascular disease during the COVID-19 pandemic.